AB0810-PC Even short term treatment with nsaids may be unsafe: the feasibility of replacing the nsaid prescription with regular paracetemol. (23rd January 2014) - Orr, C.; O'Connor, C.; McGrogan, K.
Abstract : Background: The NSAID prescription is prevalent in patients seen in primary care with rheumatic and musculoskeletal problems (1 ). New evidence suggests that there is a significant increase in the risk of death or myocardial infarction (MI), in patients with previous MI when given even short term treatment with NSAIDs (2 ). Although NSAIDs have been shown to be superior to paracetemol in their analgesic effect, this difference is small (3 ). Objectives: We therefore studied the prescribing of NSAIDs by duration of use, indication and the concomitant prescribing of paracetemol in a large Dublin primary care facility. The principal aim was to determine if patients could have been given a trial prescription for regular paracetemol instead of an NSAID. Methods: The clinics active patient list (n=10, 000) was studied by interrogating the practice management software, to identify patients over 50 years who had been prescribed NSAIDs for any duration, over a two month period in late 2012. All of the prescribed NSAIDs at the clinic were included. A record was kept of the indication for treatment and the duration of prescription, as well as whether the patient was also prescribed or known to be taking paracetemol. Results: 108 (45 male) patients were prescribed NSAIDs during the period of the study (ages 50-87 years). 29/108 (26.9%) were concomitantly prescribed paracetemol. This number increased for those prescribed NSAIDs for longer than one month to 17/108 (29%). The indications for NSAID were as follows; Musculoskeletal pain: 31 (29.7%); Osteoarthritis: 22 (20.4%); Pain (not specified): 19 (17.6%); Back Pain: 15 (13.9%); Miscellaneous: 10 (9.3%); Inflammatory arthritis: 7 (6.5%); Viral illness: 4 (3.7%) Conclusions: Many indications for NSAIDs in this study do not have an underlying inflammatory component. Given the indications for the prescription of NSAIDs in this study, nearly all patients would likely benefit from either a replacing the NSAID with paracetemol, or the addition of paracetemol to their NSAID prescription. Recent recommendations in treating osteoarthritis do not advocate NSAIDs over paracetemol (4 ). The authors contend that many cases could safely be prescribed paracetemol, as a trial, or in addition to their NSAID with a view to limiting the cumulative dose. References: Olsen AMS, Fosbøl EL, Lindhardsen J, Folke F, Charlot M, Selmer C, et al. Duration of Treatment With Nonsteroidal Anti-Inflammatory Drugs and Impact on Risk of Death and Recurrent Myocardial Infarction in Patients With Prior Myocardial InfarctionClinical Perspective. Circulation. 2011;123(20):2226-35. Baum C, Kennedy DL, Forbes MB. Utilization of nonsteroidal antiinflammatory drugs. Arthritis & Rheumatism. 2005;28(6):686-92. Towheed T, Maxwell L, Judd M, Catton M, Hochberg MC, Wells G. Acetaminophen for osteoarthritis. Cochrane Database Syst Rev. 2006;1(1). Hochberg MC, Altman RD, April KT, Benkhalti M, Guyatt G, McGowan J, et al. American College of Rheumatology 2012 recommendations for the use of nonpharmacologic and pharmacologic therapies in osteoarthritis of the hand, hip, and knee. Arthritis Care & Research. 2012;64(4):465-74. Disclosure of Interest: None Declared